2021
DOI: 10.3389/fonc.2021.633827
|View full text |Cite
|
Sign up to set email alerts
|

Application of New Radiosensitizer Based on Nano-Biotechnology in the Treatment of Glioma

Abstract: Glioma is the most common intracranial malignant tumor, and its specific pathogenesis has been unclear, which has always been an unresolved clinical problem due to the limited therapeutic window of glioma. As we all know, surgical resection, chemotherapy, and radiotherapy are the main treatment methods for glioma. With the development of clinical trials and traditional treatment techniques, radiotherapy for glioma has increasingly exposed defects in the treatment effect. In order to improve the bottleneck of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 127 publications
0
28
0
Order By: Relevance
“…However, these conventional radiotherapy sensitizers can cause many adverse side effects and acquired resistance. 16…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these conventional radiotherapy sensitizers can cause many adverse side effects and acquired resistance. 16…”
Section: Introductionmentioning
confidence: 99%
“…However, these conventional radiotherapy sensitizers can cause many adverse side effects and acquired resistance. 16 Recent studies have demonstrated that 3D hybrid organicinorganic compounds, known as carboranes, can have a role in the development of novel small molecules for the treatment of various types of cancer. [17][18][19][20][21] The synthetic flexibility of carboranes, along with their rigid structure and chemical stability, makes them appealing moieties for their use in cancer drug development.…”
Section: Introductionmentioning
confidence: 99%
“…A range of compounds that influence, for example, DNA repair (especially doublestrand break repair), act as radiosensitizers by increasing damage to the irradiated cells, leading to increased cell death [30]. However, these compounds present side effects that sometimes hamper their use [31]. Effective radiosensitizers should have less effect on normal tissues [21].…”
Section: Nanocarriers Encapsulating Radiosensitizersmentioning
confidence: 99%
“…Researchers have put in a lot of effort to improve the limitations in glioma radiotherapy, and nano-radiosensitizers have emerged as a promising treatment choice. Using nanotechnology to develop novel nano-sized platforms that cross the BBB and deliver a high concentration of the drugs into the tumor, thereby increasing tumor response to radiotherapy, is fast becoming an attractive approach to improve radiotherapy outcomes in these tumors (Liu et al 2017a;Xie et al 2021).…”
Section: Glioma: Challenges In Clinical Managementmentioning
confidence: 99%